Etiology, pathogenesis, and classification of and current methods of treatment for idiopathic macular holes: a review - I.P. Dovgan; Ines Buallagui; Zoya Rozanova; M.M. Umanets (Ukrainian Society of Ophthalmologists, 2023)
This review highlights the surgical treatment of idiopathic macular holes (IMHs). The paper aimed to review (1) the current methods of treatment for IMHs and (2) the prognosis for postoperative hole closure. IMHs are anatomic defects in the fovea resulting in central vision loss. Particular attention was given to studies on the etiology, pathogenesis, and classification of and current methods of treatment for IMHs. Tangential vitreous traction plays a key role in macular hole development. Macular holes are classified based on retinal slit-lamp biomicroscopy and optical coherence tomography findings. Although the available armamentarium of vitreoretinal surgeons includes a variety of techniques for treating IMHs of any size, there is no universal approach for selecting the optimal hole closure technique. Fovea-sparing techniques are feasible options for the treatment of IMHs and allow avoiding certain morphological and functional changes typical of conventional internal limiting membrane (ILM) peeling.